An Exploratory Survey of Incivility Experienced by Novice Occupational Therapists Educated Using a Servant Leadership Model - Deborah J. Bolding; Jennifer C. Radloff; Kim Dudzinski (Journal of Occupational Therapy Education, 2023)
The purpose of this study was to identify the incidence of incivility experienced by a purposive sample of novice occupational therapists who graduated from a master’s level program that focused on developing servant leaders as part of its mission. Data from this group was then compared to outcomes from a previous national survey of novice occupational therapists. Incivility in both studies was measured using the Negative Acts Questionnaire-Revised (NAQ-R). An independent samples t-test showed that NAQ-R total scores and person-related incivility subscores were significantly (p